The perspective of Supervisory Authorities in Albanian financial system: Markets standardization according to the EU directives - Bezo, Ardi; Voka, Ismet (European Journal of Multidisciplinary Studies, 2023)
The financial system in Albania is composed of two financial authorities and institutions, which in their missions have the monetary policies, issue of money, consumer protection, economic and financial stability, etc. The Albanian financial system is composed of two main entities such as the Bank of Albania and the Albanian Financial Supervision Authority. Both of these authorities have a fundamental role in the economy of the country, as they are not only the supervisors and regulators of the markets, such as the second level banks which are supervised by the Bank of Albania, as well as of the non-banking markets, such as the insurance markets, the securities markets as well as the markets of voluntary private pension funds, which are supervised by the Financial Supervision Authority. They are fundamental for the economy of the country since without the presence of these entities, the markets would be without a compass and full of complications that could distort free trade and encourage abuses and speculations against individuals, in security of banks activities and private firms. However, these regulators of these banking and financial markets, certainly in their functions of supervision and drafting of legislations, by-laws and regulations of the operation of these markets always refer to the Directives of the EU organizations. This paper will bring the perspectives and cooperation between each other, the functioning of these institutions, as well as the harmonization and implementation of different directives according to the markets, which regulate and turn the directives into legal and by-laws in our country.